Reconstitution of the immune system and clinical correlates after stem cell transplantation for systemic sclerosis - Kawashima-Vasconcelos, Marianna Y.; Santana-Gonçalves, Maynara; Zanin-Silva, Djúlio C.; Malmegrim, Kelen C. R.; Oliveira, Maria Carolina (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a chronic autoimmune disease that includes fibrosis, diffuse vasculopathy, inflammation, and autoimmunity. Autologous hematopoietic stem cell transplantation (AHSCT) is considered for patients with severe and progressive SSc. In recent decades, knowledge about patient management and clinical outcomes after AHSCT has significantly improved. Mechanistic studies have contributed to increasing the comprehension of how profound and long-lasting are the modifications to the immune system induced by transplantation. This review revisits the immune monitoring studies after AHSCT for SSc patients and how they relate to clinical outcomes. This understanding is essential to further improve clinical applications of AHSCT and enhance patient outcomes.